Prediction of The Surface roughening in Austenitic Stainless Steel Thin Foil With Various Grain Based on Heat Treatment Process for 5.0 Technology Application - Rafi Nurdwi Raharjo; Abdul Aziz; Agus Pramono; Suryana Suryana; Indah Uswatun Hasanah; Muhammad Fitrullah (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2026)
Prediction of The Surface roughening in Austenitic Stainless Steel Thin Foil With Various Grain Based on Heat Treatment Process for 5.0 Technology Application